Pengaruh Kombinasi Distraksi Cerita Bergambar dan Dukungan Orang Tua Untuk Mengurangi Kecemasan Anak Pre operasi di IBS RS Lavalette Malang - Cornelia Fransisca Christiani; Nurul Pujiastuti; Erlina Suci Astuti; Joko Wiyono (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2026)
Anxiety in children, if not addressed promptly, can interfere with their eating, drinking, and sleeping needs; therefore, it should not be ignored and must be managed immediately to prevent adverse effects on the child’s healing process. This study aims to determine the effect of a combined intervention of picture story distraction and parental support in reducing preoperative anxiety in children. This research employed a quasi-experimental design with a pre-test and post-test nonequivalent control group. The sample consisted of 34 school-aged children (6– 12 years old) selected through purposive sampling. Data were analyzed using the Wilcoxon Signed-Rank Test. The results showed that in the intervention group, the mean pre-test anxiety score was 50.67, with a range of 41.60 to 68.40, which significantly decreased to a post-test mean score of 25.99, ranging from 23.34 to 28.40. A p-value of 0.000 (< 0.05) indicated a significant effect of the combined intervention in reducing preoperative anxiety in children. The results of the study showed a decrease in anxiety scores after the combined therapy was administered. This approach can be utilized by nurses as a non-pharmacological strategy to create a more comfortable preoperative environment for children.